2017
DOI: 10.1590/s1678-9946201759087
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasitism among waste pickers in Mato Grosso do Sul, Midwest Brazil

Abstract: The purpose of this study was to estimate the prevalence of intestinal parasites in both cooperative-affiliated and independent waste pickers operating at the municipal sanitary landfill in Campo Grande, Mato Grosso do Sul, Brazil, and associate these findings with hemoglobin, eosinophils, vitamin A and C levels and interleukin 5 and 10 (IL-5 and IL-10) production. Biological samples were collected, in addition to clinical, epidemiological, and sociodemographic data. Stool analyzes were based on sedimentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…40,41 In Brazil, the number of incidences of intestinal parasitosis related to serum eosinophils is scare, a study with 66 garbage collectors showed eosinophils >8% was 17% of the sample, and this number was not related to parasitosis. 42 We observed that this eosinophil group presented the higher mean value of 6MWD with the same lung function parameters to other groups. This can be associated to the lower rate of the previous exacerbation rate.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…40,41 In Brazil, the number of incidences of intestinal parasitosis related to serum eosinophils is scare, a study with 66 garbage collectors showed eosinophils >8% was 17% of the sample, and this number was not related to parasitosis. 42 We observed that this eosinophil group presented the higher mean value of 6MWD with the same lung function parameters to other groups. This can be associated to the lower rate of the previous exacerbation rate.…”
Section: Discussionsupporting
confidence: 58%
“…40 , 41 In Brazil, the number of incidences of intestinal parasitosis related to serum eosinophils is scare, a study with 66 garbage collectors showed eosinophils >8% was 17% of the sample, and this number was not related to parasitosis. 42 …”
Section: Discussionmentioning
confidence: 99%
“…Giardia duodenalis infections followed distinctive gender- and age-related distribution patterns, being significantly more frequent in males than in females and children younger than ten years of age than in older subjects. The observed predominance of giardiasis in male subjects may be linked to unidentified behavioural or occupational habits [ 65 , 66 ]. Also, reporting of gastrointestinal symptoms was significantly higher in individuals with light to moderate Giardia infection burdens than in heavily infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Our systematic literature search yielded 1694 manuscripts using the established search strategies. As per the eligibility criteria (after exclusion of duplicate texts and articles related to other topics and exclusion of text based on review criteria or owing to method quality), 182 studies were selected for analysis ( Table 1 ) [ 2 4 , 6 , 7 , 9 – 25 , 27 37 , 39 , 40 , 42 45 , 47 – 56 , 58 , 60 63 , 65 – 69 , 71 , 72 , 74 , 75 , 77 – 83 , 85 93 , 95 – 104 , 106 109 , 111 , 114 – 123 , 125 130 , 132 , 135 , 136 , 138 140 , 142 – 146 , 148 – 150 , 153 164 , 167 , 169 – 173 , 175 192 , 194 204 , 207 210 , 212 – 215 , 217 219 ]. Of these studies, 166 evaluated the prevalence of Entamoeba spp.…”
Section: Resultsmentioning
confidence: 99%